AKIBAT HUKUM TERHADAP PEMAKAIAN NAMA MEREK YANG MEMILIKI PERSAMAAN PADA POKOKNYA (Ditinjau dari Undang-Undang No 20 Tahun 2016 Tentang Merek dan Indikasi Geografis) - Edy Sumarno; Salsabillah Widya Eka Putri (Bajang Institute, 2025)
This study discusses the legal consequences arising from the use of brand names that are substantially similar to other registered trademarks, as reviewed under Law Number 20 of 2016 concerning Trademarks and Geographical Indications. In practice, this phenomenon often leads to disputes between business actors, as the use of similar marks can cause confusion among consumers and harm the rightful trademark owners. The purpose of this research is to understand the legal impacts imposed on the infringers and to explain the forms of legal protection available to registered trademark owners.This study employs a normative juridical method, using statutory and case study approaches. The data analyzed comes from primary and secondary legal sources. The findings indicate that the use of a mark that has substantial similarity to a registered trademark constitutes a violation of intellectual property rights and may result in criminal, civil, and administrative sanctions as stipulated by the law. Additionally, trademark owners have the right to file lawsuits for cancellation, damages, and cessation of the infringing trademark use